DIVERSIFICATION AS A TOOL OF ANTI-CRISIS STRATEGY OF DEVELOPMENT OF RURAL TERRITORIES IN UKRAINE - Arthur Ilnitsky (Baltic Journal of Economic Studies, 2015)
The main goal of this work is to study the problems of rural development in a crisis situation and shows one of the outputs of the socio-economic problems of rural development, namely the proposed diversification of production and services. Because increased competition in the market requires a search for new effective ways and methods to ensure the survival of enterprises in rural areas in a market environment. One of these methods is the introduction of diversification. Diversity own economic and financial activity of various branches in rural areas is carried out not only in the context of globalization of the world economy associated with the interpenetration of capital and technology, but also in times of crisis as a tool of anti-crisis strategy. The effectiveness of its implementation depends on the timely focus on the types of goods and services that are in demand or close to the level of competitiveness. The question of the development strategy involving the development of methods of receiving, processing and communication of information related to the development of new technologies, products, markets and other areas and activities, as well as identify patterns to determine the motivation of diversification as a development strategy in rural areas. The methodological basis for the development of this paper, aimed at the development of rural areas in all its multidimensionality become fundamental research and active discussions among qualified experts and stakeholders, and formed on their basis of decisions of state and local governments targeted the development of production capacity, improve the quality of the environment and improving the quality of human capital in rural areas of Ukraine. Result. Diversification of economic activities in the rural development is not only adequate response to the challenges of a globalizing world economy associated with the interpenetration of capital and technology, but also in times of crisis – is one of the tools of anti-crisis strategy. The effectiveness of diversification depends on timely guidance on the types of goods and services that are in demand or close to the level of competitiveness. The practical value. Thus, our proposed mechanism for developing a program of social development will help meet the needs of the population in social infrastructure, solve the problem of territorial distribution of these facilities, to develop concrete measures to improve the functioning of the social infrastructure for various purposes and most importantly – to find ways financing of such programs will allow overcoming disparities of regions of Ukraine in general and the regions and districts to provide people with jobs. Value/originality. Diversification of the rural economy is the key to a significant decrease dependence on agriculture and the development of new economic activities, creating new businesses and investments. It can also help increase employment and income of rural population increased output of high value added, improving the quality of human capital and, finally, help boost rural development.